Analysis of genetic diversity in oilseed brassica germplasm through ISSR markers and isozyme profiling - Paul, Madhury; Islam, Tahmina; Hoque, MI; Sarker, RH (Bangladesh Journal of Botany, 2020)
Eleven Brassica germplasm were characterized through the application of 12 oligonucleotide Inter Simple Sequence Repeat (ISSR) primers. A total 1248 bands were amplified through polymorphic chain reaction and were visualized by agarose gel electrophoresis. Among the amplified marker bands 71.47% were polymorphic in nature and 352 bands were found to be monomorphic. The polymorphic bands of the amplified DNAs mostly ranged between 110 bp and 3 kb. Genetic distance among the germplasm ranged between 0.0468 and 0.7189. Moreover, three isozyme systems such as esterase, acid phosphatase and peroxidase were analyzed for allozyme variability that detected distinct 93 isozyme loci of which nearly 61.9% were polymorphic. Two dendrograms were constructed based on the ISSR profiling and isozyme data obtained through electrophoresis to find out the relatedness and phylogenetic relationship among the investigating Brassica germplasm. The clusters of the phylogenetic tree revealed 4 distinct groups of Brassica based upon their ISSR banding patterns and isozyme analysis. Nei’s genetic distance analysis provided strong information about the existence of variability among the germplasm of Brassica. All the germplasm was found to be clustered according to their respective species. Brassica carinata (Ethiopian mustard) showed individuality from all the germplasm studied and made a different branch in the phylogenetic tree suggesting its diverse origin. From the clustering pattern and genetic relationship obtained with ISSR markers and isozyme analysis, breeders can successfully identify the diverse germplasm from different cluster and use them in their future breeding program.